2022
DOI: 10.7759/cureus.27167
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Heart Failure: A Narrative Review

Abstract: Anemia in heart failure patients is a relatively common finding and has been linked with an increased risk of hospital admissions, morbidities, and significant mortality making its correction a significant factor in improving the quality of life and clinical outcomes in those suffering from it. This review article has discussed the multifactorial pathophysiology, including iron deficiency, longstanding inflammation, abnormal levels of human erythropoietin (Epo), and the abnormal activation of the renin-angiote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
0
7
0
1
Order By: Relevance
“…This was confirmed by the analysis of anaemia prevalence in relation to NYHA class: the higher the NYHA class, the higher the prevalence in anaemia ( Figure 1 ). When considering studies that adopted the WHO definition for anaemia, its occurrence ranged from 13.5% to 45% in patients with CHF and from 20.6% to 46% in AHF [ 2 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed by the analysis of anaemia prevalence in relation to NYHA class: the higher the NYHA class, the higher the prevalence in anaemia ( Figure 1 ). When considering studies that adopted the WHO definition for anaemia, its occurrence ranged from 13.5% to 45% in patients with CHF and from 20.6% to 46% in AHF [ 2 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a strong association between anemia and an increased risk of readmission in HF patients within 90 days [ 21 ]. Anemia is believed to exacerbate the symptoms of HF, leading to more frequent hospitalizations [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall about 25% of those with CKD develop anemia and by the time end-stage disease supervenes at least 75% are affected [428][429][430]. The prevalence of anemia in HF ranges from about 10% to 70% which is also stage-dependent [431]. In both cases anemia is associated with diminished quality of life, progression of disease, increased hospitalization rates, and higher mortality.…”
Section: Omnia Incipit In Sanguinementioning
confidence: 99%